Konsep ḥeseḏ dalam Kitab Hosea: Sebuah Analisis Teologis Tentang Kesetiaan Allah - Billy Graham Koirewoa; Novilda Anggel Yana Taopan (Sekolah Tinggi Teologi Injili Indonesia Yogyakarta, 2026)
The Book of Hosea presents a theological tension between judgment and restoration, both of which dominate God’s relationship with Israel. This issue raises questions regarding the theological basis that explains the coherence of God’s actions amid the people’s unfaithfulness. Previous studies generally interpret ḥeseḏ as love, faithfulness, restoration, or ethical demands, but have not specifically examined its theological function in explaining the relationship between judgment and restoration within the overall message of Hosea. This study aims to analyze the theological function of ḥeseḏ and its contribution to understanding God’s faithfulness in the Book of Hosea. The research was conducted through a literature review using a biblical theology approach and a theological-thematic analysis of Hosea 2:19–20; 4:1; 6:4, 6; 10:12; and 12:6. The results of the study indicate that ḥeseḏ functions as a relational category that explains the covenant crisis, the basis for divine judgment, and the possibility of the people’s restoration. This study concludes that ḥeseḏ reveals God’s consistency in upholding His covenantal commitment, such that both judgment and restoration are understood as manifestations of the same divine faithfulness. Recommendations for further research focus on an intertextual study of the development of ḥeseḏ within the Old Testament prophetic tradition.